KETRAMPILAN MEM8ACA SISWA SEKOLAH DASAR DENGAN PENDEKATAN PROSES - Kastam Syamsi (Jurnal Cakrawala Pendidikan, 2000)
The purpose 01" this study are (I) 1:0 ltnprove theelclllClllary school sl'udcnts'attitudc t()\vard teachingrC(lding~ and (2) to ilnprove the elerncHtary school~tudcnts~ rcading skills. This study was held at the students of grade4 and 5 of l\r1 inonlartani 3 Elementary SchoolYogyakarta.. T'he actions process is carried out' inon~ cycle. Oeut;raUy, this sluuywas al'rallg~tI asfollowed: (1) the goal: finding the approach inorder to improve the elementary school studentsattitude toward teaching reading and to improve theelenlentary school students reading skill,(2) time:14 classes meeting, (3) person: lecture, twoIndonesian grade fuurthanu fifth l~achc,., (4)gcn~ral actiun: planning lhus~ an.~ (a) itlClllifyillgreadingand (b) arranging the action, implementingthe action (that is the use of a reading processapproachin teachingreading including the steps ofpreparing to read, reading, responding, exploringthe tcxt, and extending the interpretation),monitoring and evaluation, and reflecting. Themonitoring instrulnents is observation sheet andfield note, whereas theinstrumenof evaluation arereading test and questioner.rhe result ofthis study are (I) basically thereadingproccss approach in tcaching rcading isable to improve the elementary schoolstudents'reading skill and their attitude towardteaching reading,(2) at the first step of readingprocess the student did not have opportunities tochoose the text themselves, and(3) the impacts ofthe inlplementing the action is students haveparticipate at speaking and writing activities sothey can improve their language skills